Women’s Body Objectification Under Capitalist Ideas of Beauty in Japanese Society Portrayed in The Novel Breasts and Eggs by Mieko Kawakami - Nur Prihatina, Yoshinta; Istiani, Imas (Humanis, 2025)
Capitalistic ideas of beauty in Japanese society are found in how beauty is perceived as social demand and necessity. This study attempts to reveal how the perception of women’s body and beauty in Breasts and Eggs is heavily influenced by the patriarchal and capitalistic ideals. We argue that capitalistic ideas shape the objectification of women’s bodies by using Naomi Wolf’s concept on the Beauty Myth and Alison Jaggar’s theory of capitalist feminism. It finds the female characters embody capitalist beauty standards set by the society through cosmetic surgery, media influences and societal judgment. The female character’s insecurity due to the capitalistic standards of beauty encourage her to follow beauty procedures such as breast augmentation. It reflects that beauty is transformed into commercialism and commodity. These beauty myths and beliefs lead into the psychological effects as shown further by the character’s thoughts on puberty that is tied to social expectation.